2022
DOI: 10.1021/acsami.2c18478
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast Photothermal Actuators with a Large Helical Curvature Based on Ultrathin GO and Biaxially Oriented PE Films

Abstract: In nature, there are some amazing superfast actuations (Venus flytrap) and large-curvature helical deformations (the awn of Erodium). Although many bionic actuators have been made (electrothermal, hygroscopic, photoinduced), most of their actuations are slow and small, not comparable to the wonderful ones in nature. Here, we report an ultrafast photothermal actuator with large-curvature curling based on an ultrathin graphene oxide (GO) and biaxially oriented polyethylene (BOPE) bilayer film (thickness ∼11 μm).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…Very recently, Li et al reported an ultrafast photothermal actuator with large-curvature curling based on ultrathin graphene oxide (GO) and polymer films. Under the fast temperature-changing rate and the great difference in the coefficient of thermal expansion (CTE) of GO and polymer films, the actuator deforms rapidly and greatly with the maximum bending speed and curvature of 5300° s –1 and 22 cm –1 , respectively . However, compared with the intelligence and versatility of natural biological muscles, carbon-based soft actuators still have the shortcomings of single function and insufficient intelligence.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Very recently, Li et al reported an ultrafast photothermal actuator with large-curvature curling based on ultrathin graphene oxide (GO) and polymer films. Under the fast temperature-changing rate and the great difference in the coefficient of thermal expansion (CTE) of GO and polymer films, the actuator deforms rapidly and greatly with the maximum bending speed and curvature of 5300° s –1 and 22 cm –1 , respectively . However, compared with the intelligence and versatility of natural biological muscles, carbon-based soft actuators still have the shortcomings of single function and insufficient intelligence.…”
Section: Introductionmentioning
confidence: 99%
“…Until now, many carbon-based soft actuators with excellent performance have been developed. For example, Zhou et al proposed a multiresponsive actuator based on CNT-coated paper composites. The CNT-based actuator showed large bending actuation with a bending curvature up to 1.6 cm –1 , which outperforms most other CNT-based actuators .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Soft photothermal actuators have gained significant attention due to their great applications in artificial muscles, switches, microsensors, and biomimetic devices. The development of materials with strong photothermal conversion has led to the efficient implementation of photothermal actuators. Inorganic carbon nanomaterials, such as carbon nanotubes, graphene, and MXene, are commonly used in photothermal actuator research. Despite the excellent photothermal conversion and soft mechanical properties of organic crystal materials, there has been limited research on the construction of soft photothermal actuators utilizing these materials . Hence, exploring the potential application value of organic crystal materials in soft photothermal actuators is an attractive and promising avenue for future research.…”
Section: Introductionmentioning
confidence: 99%
“…Flexible actuators based on the various adaptive mechanical responses of organisms to external stimuli in nature are desirable. Creating flexible actuators that exhibit controllable and programmable shape transformations in response to environmental stimuli would enable broad scientific and engineering applications, such as flexible robots, biomedical devices, and smart wearable devices. Although magnetically driven flexible electronic devices have the advantage of rapid and fatigue-resistant actuation, their large size and fixed stiffness restrict their ability to undergo large-scale deformation; pneumatically driven actuators based on silicone elastomers and rubber have high degrees of freedom and superior power density, but there is still a challenge in balancing manufacturing cost with precise control; carbon-based electrothermal or photothermal actuators exhibit significant deformation under electrical or optical stimulation, which are primarily driven by the difference in thermal expansion of the bilayer structure. However, these actuators are limited to thermal expansion and increasing their deformation further is difficult.…”
Section: Introductionmentioning
confidence: 99%